Continuous synthesis and scaled shaping of archetypal metal-organic frameworks for carbon capture applications - Oakley, William (2024)
The research presented in this thesis focuses on the holistic advancement of archetypal metal-organic frameworks (MOFs) towards post-combustion carbon capture applications. Advancements are made to develop continuous synthesis routes for previously batch produced carbon capture frameworks and to produce practical MOF macroscopic structures ready for industrial application. Importantly, where possible these novel methodologies were demonstrated at industrially relevant scales, with examples ranging from multi-gram to multi-kilogram scales achieved. This has enabled the direct utilisation of the materials produced within bespoke carbon capture systems, ranging from bench scale to an industrial pilot unit evaluated in field trials at Drax Power Station.